HUKUM VAKSIN MEASLES RUBELLA (Analisis Fatwa MUI Nomor 33 Tahun 2018) - Wahyu Fadhilatul Hikmah; Zainal Azwar (Jurnal AL-AHKAM, 2020)
The Muslim community was shocked by the government policy regarding Measles Rubella (MR) vaccine which has been proven to contain haram elements. Muslims are increasingly uneasy and confused by the central MUI fatwa that approves the use of MR vaccine is allowed on emergency grounds. This paper analyzes the MUI fatwa number 33 of 2018 regarding the ability to use the MR vaccine for reasons are darurat so itjustifies something is prohibited. The method used is descriptive qualitative and it is library research. The use of reasons darurat to allow the use of vaccines that are clearly haram &prohibited is inappropriate, MUI uses the excuse of rats being too light. MR plagues in Indonesia cannot yet be determined as conditions of extraordinary conditions or circumstances which can threaten the survival of one of the objectives of the shari'ah which is to save lives. There is no certainty and concrete data that explain the state of the MR epidemic in Indonesia. The criteria for the condition of darurat so the haram can be breaked are as follows: darurat has occurred, it is ensured that by doing what is illegal can eliminate the danger,being forced because there is no other way for the loss of dharar,haram is lighter than the danger that will befall, darurat does not contradict with the principles of Islamic law, something that is haram or forbidden to be consumed when it is taken modestly,regard totreatmentthere must be a statementfrom a competent doctor in terms of illness and treatment for which there is no medicine other than that which is haram according to syara',the situation of darurat is not limited in time, andthere must be an official statementrelating to the darurat from the government of a country.